PEMANFAATAN MEDIA SOSIAL DALAM PENGEMBANGAN USAHA ONLINE SHOP MORIVIAN DI PAYAKUMBUH - Maisyarah Suardi; Khadijah Nurani (ADISAM PUBLISHER, 2023)
In improving the economy, digital technology has a very important role in providing and fulfilling the goods and services that humans need. To promote products, sell products and share information on services provided by an online business, digital technology acts as a platform to promote products through social media. Online shops usually offer their goods by mentioning the specifications of the goods, prices, and pictures. This research method is qualitative with field research. Data collection techniques are through observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, data triangulation and conclusion drawing (verification). Based on the results of research on the utilization of social media used in business development, it is very easy for consumers to get the information they want. done on increasing activities in the use of social media, getting trusted and safe distributors in supplying products, providing interesting content to attract consumers, communicating smoothly with consumers in social media chat rooms, being able to sell with features available on social media and being able to increase capital. Obstacles in developing an online shop business include the inconsistency of business owners in utilizing their social media, each item must pass an order that takes a long time, the cancellation of orders